Public service broadcasting of sport, shows, and news as economic solution to the voter's paradox of rational ignorance - Julia Rothbauer; Gernot Sieg (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2010)
Rational individuals may use a Public Service TV channel as a welfare improving institution to solve the paradox of being uninformed. To induce voters to watch unbiased serious informational content the Public Service TV channel is not only broadcasting (unbiased serious) news but also sport and shows even though in many markets sport and shows are broadcasted by private TV channels. Our approach is based on two-sided markets and the assumption of decreasing marginal returns of the factor information in the production process of democratic decisions.
Keywords: L82; D72; L32; 330; Media Industry; voter behavior; two-sided markets; education